PERBANDINGAN BUERGER ALLEN EXERCISE DENGAN FOOT SPA DIABETIC TERHADAP NILAI ANKLE BRACHIAL INDEX PADA PASIEN DIABETES MELITUS TIPE II - Ibrahim, Iksan; Sofiani, Yani; Irawati, Diana (Journal of Islamic Nursing, 2020)
Hyperglycemia is one of the problems of Diabetes Mellitus patients. Hyperglycemia that is not well controlled can cause many complications, one of which is interference with the flow of peripheral blood vessels that can cause diabetic ulcers. Vascularity disorders can be prevented with Buerger Allen Exercise therapy and Diabetic Foot Spa to increase the value of ABI. The purpose of this study was to compare the effectiveness of Buerger Allen Exercise therapy and Diabetic Foot Spa to the value of ABI in patients with type II diabetes mellitus. The design of this study was Quasi Experiment Pre and post test two groups with 15 group A respondents given Buerger Allen Exercise intervention and 15 group B respondents given Diabetic Foot Spa intervention. The results showed that there was an increase in the value of ABI after intervention in both groups with the difference in the increase in the Buerger Allen Exercise group by 0.050 while the Diabetic Foot Spa group by 0.113. The conclusion of this study is that there was an increase in ABI values in both groups after the intervention but the Diabetic Foot Spa group had a higher increase. Diabetic Foot Spa can be recommended as an alternative therapy as prevention of peripheral arterial disease complications.